Learning oriented assessment : a systemic approach - Jones, Neil, Dr; Saville, Nick (United Kingdom : Cambridge University Press, 2016)
'This volume outlines the general principles of Learning Oriented Assessment (LOA), placing it in the context of European language learning policy. The authors pose three key questions central to LOA:'What is learning?','What is to be learned?' and'What is to be assessed?'. It focuses on the use of evidence, and how it can be collected and used to feed back into learning, overviews large-scale assessment as practised by Cambridge English and learning-oriented classroom assessment practices, and concludes with a look at implementing LOA in practice. With fresh insights into the role of assessment in supporting learning, this volume will be of considerable interest to assessment practitioners, teachers and academics, educational policy-makers and examination board personnel'-- Provided by publisher'This volume outlines the general principles of Learning Oriented Assessment, placing it in the context of European language learning policy and its role in recent practical and theoretical developments in language assessment'-- Provided by publisher
List of tables and figuresx Abbreviationsxi Acknowledgementsxii Series Editors' notexiv1.Learning Oriented Assessment: An overview11.1.The organisation of this volume61.2.What is learning?71.3.What is language learning?81.4.What is to be learned?91.5.The roles of assessment in learning101.6.Aligning large-scale and classroom assessment121.7.In summary142.The roots of Learning Oriented Assessment152.1.Cambridge English and Learning Oriented Assessment162.2.Origins and emphases of learning-oriented approaches162.3.Defining learning-oriented assessment: Process, policy or principles?242.4.Specific learning-oriented methods283.What is learning?303.1.Constructivism303.2.An appropriate model of cognition and learning323.3.Task-based interaction333.4.Roles of teachers and learners413.5.In summary464.What is language learning?484.1.Languages as a special case484.2.The Common European Framework of Reference for Languages494.3.Natural language acquisition514.4.Second Language Acquisition research514.5.In summary575.What is to be learned?585.1.The desired outcomes of learning585.2.The nature of language proficiency: Construct definition625.3.The content of learning: Curricular objectives655.4.In summary666.The role of large-scale assessment in learning686.1.Proficiency testing: The importance of criterion reference696.2.Scale construction706.3.Item Response Theory716.4.Item banking726.5.Performance assessment746.6.Validity and reliability of large-scale assessment756.7.Large-scale assessment: Evidence of and for learning786.8.In summary797.Learning-oriented assessment in the classroom817.1.The nature of classroom learning-oriented assessment817.2.Domain-specific and generalisable learning skills827.3.Learning-centred and content-centred activities837.4.Classroom evidence of and for learning847.5.Learning-oriented assessment: An ecological model887.6.In summary918.Aligning large-scale and classroom assessment938.1.Alignment of goals938.2.Aligning interpretations of standards948.3.Construct-based alignment of assessment978.4.Evidence within a Learning Oriented Assessment model1008.5.The validity of Learning Oriented Assessment1039.Implementing Learning Oriented Assessment1069.1.Educational policy-making: The global scale1069.2.Worlds of difference: Predictable implementation issues1079.3.Asset Languages: A cautionary tale1099.4.Technology to the rescue?1109.5.New contexts of learning1119.6.Positive impact by design1139.7.Steps in implementation1179.8.A conclusion118 Appendices Appendix 1Assessment for learning: 10 principles (Assessment Reform Group 2002)122Appendix 2The Teaching and Learning Research Programme (TLRP): 10 principles of effective pedagogy (Teaching and Learning Research Programme 2007)125Appendix 3James and Pedder's (2006) hypotheses on assessment for learning127 References128 Author index140 Subject index144
Includes bibliographical references (pages 128-139) and indexes.
Koleksi sumbangan Tun (Dr.) Ahmad Sarji Abdul Hamid.
Keywords: Language and languages -- Examinations; Language and languages; Education, Higher -- Evaluation; Educational tests and measurement; Communication in education